2004
DOI: 10.1074/jbc.m407820200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Substrate Recognition in Hematopoietic Protein-tyrosine Phosphatase

Abstract: The extracellular signal-regulated protein kinase 2 (ERK2) plays a central role in cellular proliferation and differentiation. Full activation of ERK2 requires dual phosphorylation of Thr 183 and Tyr 185 in the activation loop. Tyr 185 dephosphorylation by the hematopoietic protein-tyrosine phosphatase (HePTP) represents an important mechanism for down-regulating ERK2 activity. The bisphosphorylated ERK2 is a highly efficient substrate for HePTP with a k cat /K m of 2.6 ؋ 10 6 M ؊1 s ؊1 . In contrast, the k c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 54 publications
6
33
1
Order By: Relevance
“…This observation is supported by kinetic studies of HePTP that demonstrated that the catalytic activity of HePTP towards phosphorylated substrates increased by one to two orders of magnitude when Thr106 was mutated to either aspartic acid or asparagine. 31 Because this increase in catalytic efficiency was observed towards only phosphorylated peptides and not towards the biphosphorylated Erk2 protein (Erk2/pTpY), Thr106 has been postulated to function as a negative determinant to restrict HePTP catalytic activity towards HePTP-specific substrates. 31 Second, the PTP1B peptide recognition loop residue Arg47 interacts extensively with both the backbone and side-chains of the bound EGFR peptide residues.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is supported by kinetic studies of HePTP that demonstrated that the catalytic activity of HePTP towards phosphorylated substrates increased by one to two orders of magnitude when Thr106 was mutated to either aspartic acid or asparagine. 31 Because this increase in catalytic efficiency was observed towards only phosphorylated peptides and not towards the biphosphorylated Erk2 protein (Erk2/pTpY), Thr106 has been postulated to function as a negative determinant to restrict HePTP catalytic activity towards HePTP-specific substrates. 31 Second, the PTP1B peptide recognition loop residue Arg47 interacts extensively with both the backbone and side-chains of the bound EGFR peptide residues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hematopoietic protein-tyrosine phosphatase (HePTP), mitogen-activated protein kinase phosphatase-3 (MKP3), and protein serine/threonine phosphatase 2A (PP2A) can all act as ERK2 phosphatases (Zhou et al, 2002a). Although ERK2 activity can be terminated by Tyr 185 dephosphorylation with high efficiency and fidelity by HePTP (Huang et al, 2004), PP2A regulates a wide variety of cellular signal transduction pathways, including the Raf1-MEK1/2-ERK1/2 signaling pathway at multiple steps, and can act as a negative or positive regulator of ERK1/2 activity (Zhou et al, 2002a;Ory et al, 2003).…”
Section: Mapkmentioning
confidence: 99%
“…Finally, it is important to note that interactions between the docking site and the KIM sequence alone may be only partially responsible for recognition of effector molecules by the MAP kinases (12,16). The role of the KIM͞docking site interaction is to increase the ''effective concentration'' of the interacting molecules (21,32). In addition to this ''tethering'' effect, additional interactions between the MAP kinases and their regulators and substrates (e.g., phosphorylation lip with MAP kinase͞ERK kinases and MKPs, and substrate binding region with the phosphorylation sequence in the substrates) are required to confer the exquisite specificity in MAP kinase signaling (16).…”
Section: Map Kinases Share a Common Docking Sitementioning
confidence: 99%